Navigating Change: Experiences of Digitalisation Projects Within the Swedish Transport Administration - Fredrik Molin; Eva Norrman Brandt (Administrative Sciences)
Background: Digital transformation has emerged as an important theme in contemporary organisational studies, particularly within public sector institutions striving to enhance operational efficiency, improve service delivery, and foster innovation. This study aimed to explore the experiences of key actors within the Swedish Transport Administration, focusing on the challenges and opportunities associated with digital transformation. The research questions were as follows: (1) How do key actors perceive the effectiveness of the organisation’s management control systems in supporting digitalisation efforts? (2) What challenges and opportunities do key actors identify in the project management approach for implementing digital transformation initiatives? (3) How do key actors view the alignment between project-level goals and the Administration’s overarching strategic goals for digitalisation? Methods: The study employed a qualitative approach, conducting semi-structured interviews (n = 18) with participants from the Administration. Data from the interviews were analysed using an open coding approach. Results: The findings revealed that (1) respondents favour a more centralised and cohesive approach to management control, (2) there is a notable lack of expertise in change management, and (3) alignment between strategic and project-level objectives is insufficient, creating challenges in ensuring consistency and coherence in the implementation of digitalisation efforts. Conclusions: The results shed light on issues regarding management control, prioritisation, and the coordination of digitalisation efforts within a public sector administration.